An experimental study of the recovery of injured porcine lungs with prolonged normothermic cellular ex vivo lung perfusion following donation after circulatory death. (19th July 2017) - Spratt, John R.; Mattison, Lars M.; Iaizzo, Paul A.; Brown, Roland Z.; Helms, Haylie; Iles, Tinen L.; Howard, Brian; Panoskaltsis‐Mortari, Angela; Loor, Gabriel
Summary: Donation after circulatory death (DCD) is an underused source of donor lungs. Normothermic cellular ex vivo lung perfusion (EVLP) is effective in preserving standard donor lungs but may also be useful in the preservation and assessment of DCD lungs. Using a model of DCD and prolonged EVLP, the effects of donor warm ischemia and postmortem ventilation on graft recovery were evaluated. Adult male swine underwent general anesthesia and heparinization. In the control group ( n = 4), cardioplegic arrest was induced and the lungs were procured immediately. In the four treatment groups, a period of agonal hypoxia was followed by either 1 h of warm ischemia with ( n = 4) or without ( n = 4) ventilation or 2 h of warm ischemia with ( n = 4) or without ( n = 4) ventilation. All lungs were studied on an EVLP platform for 24 h. Hemodynamic measures, compliance, and oxygenation on EVLP were worse in all DCD lungs compared with controls. Hemodynamics and compliance normalized in all lungs after 24 h of EVLP, but DCD lungs demonstrated impaired oxygenation. Normothermic cellular EVLP is effective in preserving and monitoring of DCD lungs. Early donor postmortem ventilation and timely procurement lead to improved graft function.